Diagnosis and treatment of coronary spasm in China: a case report - Zhang, Hongyang; Ye, Xianglin; Pei, Haifeng (Frontiers in Cardiovascular Medicine, 2024)
Background: Coronary vasospasm (CVS) is a common cardiovascular condition, yet its implications should not be underestimated. Regrettably, the current diagnostic and treatment standards for CVS in China are not standardized, severely affecting the quality of life for patients with this condition.Case Presentation: A 68-year-old male presented to the hospital one month prior due to recurrent chest pain. Coronary angiography (CAG) revealed a mid-segment muscle bridge with plaque formation in the left anterior descending artery, followed by pharmacological balloon angioplasty.The primary diagnosis post-operation was acute non-ST elevation myocardial infarction (NSTEMI) and coronary artery myocardial bridging. This time, the patient experienced nocturnal chest pain with a dynamic increase in troponin levels. Emergency CAG showed the left anterior descending and right coronary arteries were fine, with segmental narrowing reaching 95-99%. Intravascular ultrasound (IVUS) indicated negative remodeling of the mid-segment lumen associated with myocardial bridging, with the smallest lumen area being 2.19mm 2 . After intracoronary administration of nitroglycerin, the original most narrowed lumen area increased to 8.81mm2.Consequently, a definitive diagnosis of CVS with coronary artery myocardial bridging was made, and the medication treatment plan was promptly adjusted. The patient's symptoms disappeared, and he was discharged. Follow-up after more than three months showed no recurrence of symptoms.In cases where provocative agents are contraindicated, CAG combined with IVUS can optimize the differential diagnosis of CVS. There is an urgent need in China to improve epidemiological data on CVS and establish standardized diagnostic and treatment protocols.